Description of the Characteristics of Long-Acting Contraceptive Method Users in the Working Area of Aimere Health Center, Ngada Regency - Nau, Maria Yolanda; Nayoan, Christina; Sir, Amelia B (Faculty of Public Health, Nusa Cendana University, 2024)
Long-acting contraceptive methods (LACMs) have a higher level of effectiveness compared to other family planning methods. The coverage of LACM acceptors in the working area of Aimere Health Center from 2019 to 2021 has shown a significant increase, with implants being the most commonly used method (57.14%), while the use of IUDs remains very low (2.43%). This study aims to describe the characteristics of LACM acceptors in the working area of Aimere Health Center, Ngada Regency. A quantitative descriptive method with a survey design was employed. The study population included 566 LACM acceptors, and a sample of 85 respondents was selected using a simple random sampling technique. The data were analyzed using frequency distribution. The results showed that the majority of LACM acceptors used implants, accounting for 67 respondents (78.8%). Most of the acceptors were aged 36–49 years (54 respondents, 64.7%), had completed senior high school (36 respondents, 42.4%), worked as farmers (53 respondents, 62.4%), had more than two children (59 respondents, 69.4%), and had low knowledge about LACMs (50 respondents, 58.8%). It is recommended that health workers enhance educational outreach in communities to improve public knowledge about contraceptive methods and dispel negative perceptions associated with long-acting contraceptive methods such as IUDs and sterilization.